DIVIDEND POLICY AS MEDIATION OF THE INFLUENCE OF MANAGEMENT OWNERSHIP AND INSTITUTIONAL OWNERSHIP ON COMPANY’S FINANCIAL PERFORMANCE - Supriyono -; Dian Wismar’ein (Conference In Business, Accounting, And Management (CBAM), 2015)
The purposes of this research are: (1) to examine if management ownership influences significantly positive on dividend policy (2) to examine if institutional ownership influences significantly positive  on  dividend  policy,  and  (3)  to  examine  if  dividend  policy influences significantly positive on company’s financial performance. This is an explanatory research since it aims to explain the influence among variables after testing  research  hypotheses  based  on  the  underlying  theory.  The  data  of  this  research  are financial reports of go public manufacture companies which have been audited at Indonesian Stock  Exchange  (IDX)  from  2003  –  2012.  This  is  a  census  research  that  is  by  using  all population, 36 manufacture companies. Since this is a census research by using pooling data technique for 10 years so there were 360 observation data. This research used path analysis technique to test hypotheses. The research finding shows that management ownership doesn’t influence significantly positive on dividend policy, institutional ownership doesn’t influence significantly positive on dividend policy, dividend policy doesn’t influence significantly positive on company’s financial performance,  Keywords : dividend policy, management ownership, institutional ownership, and company’s financial performance